Cesarean birth Ogilvie Syndrome: a case report - Araújo Medeiros Vila Nova, Carolina; de Oliveira Nascimento Monteiro, Caroline; da Silva Cardoso, Jacqueline; Andreia Martins Moreno, Keila; Tenório Lins Carnaúba, Aline (Seven Editora, 2023)
The intestinal motility disorders during pregnancy may present adynamia, which may be confused with intestinal occlusion symptoms. Most of the time the benign evolution, however, may also show the intestinal pseudo-obstruction, also known as Ogilvie  Syndrome, first described by the surgeon Heneage Ogilvie in 1948, through specific signals and symptoms and radiological findings, such as abdominal distention, nausea,  vomiting, and colon dilation, simulating intestinal occlusion with no apparent mechanical cause. In the case reported, the patient was a 32-year-old breastfeeding woman, with postpartum complications,  who developed Ogilvie Syndrome, in which the late diagnosis resulted in an acute intestinal pseudoobstruction of the colon after having undergone emergency surgery.    This report aims to emphasize such syndrome among the postpartum complications diagnosed,  following surgical delivery,  so that early treatment and medical assistance may be provided to the patient, avoiding any unwanted outcome. DOI: https://doi.org/10.56238/devopinterscie-103